Solution of two-body bound state problems with confining potentials - Hadizadeh, M. R. [UNESP]; Tomio, Lauro [UNESP] (AIP Publishing, 2010)
The homogeneous Lippmann-Schwinger integral equation is solved in momentum space by using confining potentials. Since the confining potentials are unbounded at large distances, they lead to a singularity at small momentum. In order to remove the singularity of the kernel of the integral equation, a regularized form of the potentials is used. As an application of the method, the mass spectra of heavy quarkonia, mesons consisting from heavy quark and antiquark (Υ(bb̄), ψ(cc̄)), are calculated for linear and quadratic confining potentials. The results are in good agreement with configuration space and experimental results. © 2010 American Institute of Physics.
Keywords: confining potential; Lippmann-Schwinger integral equation; two-body problem